The Role of Ashwagandha in Exercise Performance and Recovery: An Evidence-Based Review - Komorowski, Marcin; Janiszewski, Michał; Szatkowska, Dorota; Ziętara, Dominika; Kmieć, Kacper; Topolska, Aleksandra; Wilska, Hanna; Surosz, Natalia; Grochowalski, Michał; Graczyk, Aleksandra; Szydło, Jakub (Quality in Sport, 2025)
Background: Withania somnifera (Ashwagandha) is a well-known adaptogenic herb with a growing body of evidence supporting its role in enhancing physical performance. This review aims to evaluate the effects of Ashwagandha supplementation on key aspects of exercise capacity, including aerobic performance, muscle strength, and post-exercise recovery. Material and methods: A literature review was conducted using databases such as PubMed and Google Scholar, including studies from 2012 to 2025 that examined the effects of Ashwagandha supplementation in physically active individuals. Results: Most randomized controlled trials report that daily supplementation with Ashwagandha (500–1250 mg) over 8–12 weeks leads to significant improvements in VO₂max, muscular strength, and time to exhaustion. Additional benefits include reduced cortisol levels, improved recovery rates, and decreased markers of muscle damage and inflammation. Positive effects were observed in both trained and untrained individuals. Conclusions: Ashwagandha supplementation appears to support various aspects of physical performance and recovery, offering practical value for both amateur and professional athletes. However, limitations such as small sample sizes and variability in study design highlight the need for further research to confirm these findings and better understand the underlying mechanisms. Keywords: Ashwagandha, Withania somnifera, physical performance, endurance, strength, recovery, supplementation, adaptogen